2015
DOI: 10.3389/fnagi.2015.00141
|View full text |Cite
|
Sign up to set email alerts
|

“Are we ready for robots that care for us?” Attitudes and opinions of older adults toward socially assistive robots

Abstract: Socially Assistive Robots (SAR) may help improve care delivery at home for older adults with cognitive impairment and reduce the burden of informal caregivers. Examining the views of these stakeholders on SAR is fundamental in order to conceive acceptable and useful SAR for dementia care. This study investigated SAR acceptance among three groups of older adults living in the community: persons with Mild Cognitive Impairment, informal caregivers of persons with dementia, and healthy older adults. Different tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
220
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(241 citation statements)
references
References 57 publications
11
220
2
8
Order By: Relevance
“…A mismatch between needs and the solutions offered by robots are a barrier to acceptance and robot adoption [20]. Hawkey et al (2005) found carers and PWD disagreed as to what they wanted from a robotic device designed to help deal with repeated questioning.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
See 2 more Smart Citations
“…A mismatch between needs and the solutions offered by robots are a barrier to acceptance and robot adoption [20]. Hawkey et al (2005) found carers and PWD disagreed as to what they wanted from a robotic device designed to help deal with repeated questioning.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
“…In order to be accepted, social robots need to be perceived by users as useful and relevant to their current unmet needs [18,19,20,21,22]. A mismatch between needs and the solutions offered by robots are a barrier to acceptance and robot adoption [20].…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a study carried out by Hayley et al [3] showed that users were enthusiastic and had positive attitude towards the use of Paro because the users believed that Paro was beautiful looking, life-like, tactile and had lovely eyes. [53] emphasized that hyper-realistic representations of robots with human appearance could lead persons with dementia to confusion. Hence, the use of such robots in the provision of therapy for patients is a challenge.…”
Section: B Usability Challengesmentioning
confidence: 99%
“…Nevertheless, two issues were realized regarding living with a human-type communication robot as a strategy; to improve cognitive functions and prevent cognitive decline in the elderly [12]. With robot therapy, it was found that only a few aspects of its capabilities, when examined closely, were effects derived from the viewpoints of nursing practices and human care [13] [14]. In this regard, robot therapy has not been generalized, and more descriptions and discussions about its practical utility are required.…”
Section: Introductionmentioning
confidence: 99%